STRATEGIC LEADERSHIP OF THE PRINCIPAL IN DECISION MAKING IN PRIMARY SCHOOLS IN MEULABOH - Rosmaniar; Siti Mayang Sari; Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study aims to examine the leadership of school principals in making decisions about disciplinary violations in elementary schools. This research uses qualitative research with case study method. The subjects of this study were teachers, principals, and students. Data was collected through interviews and observations. The results of this study show: 1) the head decision-making process by identifying problems by knowing the types of disciplinary violations, grouping the types of violations of discipline by students or teachers, then finding and deciding on the types of sanctions and solutions for the types of disciplinary violations, providing sanctions in accordance with the form of mistakes that have been made, 2) the decision-making process based on the causes of problems. The principal must understand educators and students; pay attention to violations looking for reasons for violations committed by students and educators; search and find the elements that cause students and educators to violate discipline; and explain and find the cause of the violation. 3) The decision-making process is carried out by the Head of the School by knowing the type of violation and the consequences caused, supervising teachers and students, establishing communication and socialization to students to always maintain cleanliness; encourage active participation of teachers to build student character and behavior, and inform teachers not to show bad behavior to students.